FRAKTAL: ALIH WAHANA KONSEP AIR DALAM KEBUDAYAAN SUNDA PADA KARYA TARI - Azhar, Angeline (Jurnal Kajian Seni, 2025)
The process of creating a dance work entitled Fractal stems from research on water in Sundanese culture. The creation of this dance work uses a practice-based research method. This research explores the symbolism of water in the traditions and daily lives of Sundanese people, which includes rituals, mythology, and agricultural practices. In the creative process, researchers collect data through observation, interviews, and literature review, which are then interpreted into dance movements. The stages of creation began with the exploration of basic movements inspired by the shape and dynamics of water, followed by improvisation involving dancers to explore the meanings and emotions associated with water. The results of this research are realised in a dance work that reflects the harmony, sustainability and spirituality of water in the lives of Sundanese people. This process shows that through a practice-based research approach, research becomes a scientific foundation that inspires and enriches the creation of dance art, while deepening understanding of local cultural values. This research not only produces aesthetic works of art but also raises and carries out the process of sustainability of local wisdom values.